Hyperandrogenism-Insulin Resistance-Acanthosis Nigricans Syndrome - A. H. Dédjan; A. Chadli; S. El Aziz; A. Farouqi (Case Reports in Endocrinology)
Introduction. Female hyperandrogenism is a frequent motive of consultation. It is revealed by hirsutism, acne or seborrhea, and disorders in menstruation cycle combined or not with virilisation signs. Several etiologies are incriminated but the hyperandrogenism-insulin resistance-acanthosis nigricans syndrome is rare. Observation. A 20-year-old girl, having had a five-year-old secondary amenorrhea. The exam revealed a patient, normotensive with a body mass index at 30 kg/m2 and a waist measurement of 120 cm, a severe hirsutism assessed to be 29 according to Ferriman Gallwey scale, virilisation signs of male morphotype, clitoridic hypertrophy and frontal alopecia, and an acanthosis nigricans behind the neck, in the armpits and elbows. The assessment carried out revealed testosteronemia at 1.28 ng/mL, which is more than twice the upper norm of the laboratory. Imaging studies were negative for both ovarian and adrenal masses. The retained diagnosis is HAIR-AN syndrome probably related to ovarian hyperthecosis and she was provided with androcur 50 mg/day and estradiol pills 2 mg/day and under hygiene-dietetic conditions. Conclusion. This case proves that HAIR-AN syndrome could be responsible for severe hyperandrogenism with virilisation signs. It must be retained after discarding the tumoral causes and when there are signs of insulin resistance.